Physiological considerations for paratriathlon training and competition - Stephenson, B.; Goosey-Tolfrey, L. V. (Triathlon Medicine, 2019)
Paratriathlon is a multi-impairment, Paralympic, endurance sport with athletes` impairments typically consisting of spinal cord injury, cerebral palsy or other neurological disorders, amputations, or visual impairments. As the sport made its Paralympic Games debut only in 2016, there is a dearth of literature concerning the sport. This opposes able-bodied triathlon whereby a significant mass of information is available concerning the physiology, training habits and competitive performance of athletes. However, due to primary or secondary consequences of paratriathletes` impairments, there are many considerations that must be made when attempting to transfer information on training or competition from able-bodied triathletes. Paratriathletes may be at risk of intolerably high internal training load as movement inefficiencies augment the metabolic cost of daily ambulation and sporting performance. This can then result in a susceptibility for mucosal immunity suppression, and subsequent illness, or overreaching genesis. Likewise, paratriathletes` impairments may diminish their thermoregulatory capacity, resulting in amplified strain when competing in the heat. This has implications for all impairment types due to myriad factors that interact with heat loss or gain during races. Nonetheless, strategies, such as heat acclimation, may be utilised to ameliorate the thermal strain of competition in the heat.